2017
DOI: 10.1080/10410236.2017.1405487
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Stigma Messages: Danger Appraisal and Message Judgments

Abstract: Media coverage of health issues has been criticized for creating health stigmas. The model of stigma communication (MSC, Smith, 2007) provides insights into why this is so, but it has two problems: Some of its mediators have not been supported, and it does not do a good job of predicting the transmission of stigma messages (i.e., social transmission). We present a revised model of stigma message effects in which exposure to stigma messages leads to stigma beliefs and stigmatization as a result of a person-orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 67 publications
3
32
0
Order By: Relevance
“…The network size (19 members) and number of interpersonal connections (from 1 to 6) was consistent with studies of self-reported friendship networks (Brewer & Webster, 1999). Research using this hypothetical sociogram found that participants tended to rate it as believable (Smith, Zhu, & Fink, 2017).…”
Section: Methodssupporting
confidence: 79%
“…The network size (19 members) and number of interpersonal connections (from 1 to 6) was consistent with studies of self-reported friendship networks (Brewer & Webster, 1999). Research using this hypothetical sociogram found that participants tended to rate it as believable (Smith, Zhu, & Fink, 2017).…”
Section: Methodssupporting
confidence: 79%
“…Threats are events or actions that have the "potential of resulting in harm if they are not avoided or neutralized" across different contexts and risk issues (Smith & Lazarus, 1990, p. 614). In a health risk communication context, threat appraisal encompasses individuals' perceived susceptibility, or likelihood, to contract a disease; the perceived severity, or seriousness, of contracting an illness; and resulting information behaviors (Jeong & Lee, 2018;Rains & Tukachinsky, 2015;Smith et al, 2019;Witte, 1992). Threat appraisal is one of the key determinants of the adoption or rejection of protective behaviors, as evidenced in models that attempt to predict behavior (e.g., the extended parallel process model, Witte, 1992; the health belief model, Janz & Becker, 1984; and the uncertainty management theory, Rains & Tukachinsky, 2015).…”
Section: Threat Appraisalsmentioning
confidence: 99%
“…Responses to health threats involve a mix of affective and logical components (Reynolds, 2011). Research finds that affective reactions follow cognitive threat appraisals and are more likely to precede cognitive responses in an imminent health threat scenario (Jeong & Lee, 2018;Rains & Tukachinsky, 2015;Smith et al, 2019;So, 2013).…”
Section: Affective Copingmentioning
confidence: 99%
“…Thus, messages about health disparities share many of the characteristics that Smith (2007) described as being present in messages that communicate stigma. They draw attention to distinct groups of people defined by racial, social, or behavioral characteristics; they link these groups to a physical threat (i.e., HIV or another health condition); and by using either a comparative or individual responsibility frame, or in some cases both, they suggest indirectly or directly that group members are responsible for the threat.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy People 2020 defines a health disparity as "a particular type of health difference between individuals or groups that is unfair because it is caused by social or economic disadvantage" (U.S. Department of Health and Human Services, 2008). Despite significant progress in the prevention and treatment of HIV in the United States, disparities remain in rates of infection from stigmatized individuals, and the social transmission of stigma messages (Smith et al, 2019). Because HIV and groups at greater risk for HIV are often associated with multiple social stigmas, communication about HIV and disparities in HIV are particularly susceptible to containing characteristics of stigma messages.…”
Section: Introductionmentioning
confidence: 99%